2020
DOI: 10.3390/plants9050644
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Glycine Betaine or Hydrogen Peroxide Sprays Ameliorate Waterlogging Stress in Cape Gooseberry

Abstract: Exogenous glycine betaine (GB) or hydrogen peroxide (H2O2) application has not been explored to mitigate waterlogging stress in Andean fruit trees. The objective of this study was to evaluate foliar GB or H2O2 application on the physiological behavior of Cape gooseberry plants under waterlogging. Two separate experiments were carried out. In the first trial, the treatment groups were: (1) plants without waterlogging and with no foliar applications, (2) plants with waterlogging and without foliar applications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The first ROS to be generated is usually O − 2 , with the radicals forming H 2 O 2 spontaneously by dismutation (Mori and Schroeder, 2004). Excess H 2 O 2 production when plants are waterlogged affects multiple physiological processes because H 2 O 2 is a strong uncharged oxidant molecule (Castro-Duque et al, 2020;Cen et al, 2020). Waterlogging stress inflicts significant damage on waxy corn seedlings, as suggested by the greater levels of O − 2 and H 2 O 2 in the leaves of both the SY-MY13 and SY-XT1 inbred lines used in the current study (Figures 2C,D), which also demonstrated the histochemical staining of O − 2 and H 2 O 2 at the tissue level in the leaves of waxy corn (Figures 2A,B).…”
Section: Discussionmentioning
confidence: 99%
“…The first ROS to be generated is usually O − 2 , with the radicals forming H 2 O 2 spontaneously by dismutation (Mori and Schroeder, 2004). Excess H 2 O 2 production when plants are waterlogged affects multiple physiological processes because H 2 O 2 is a strong uncharged oxidant molecule (Castro-Duque et al, 2020;Cen et al, 2020). Waterlogging stress inflicts significant damage on waxy corn seedlings, as suggested by the greater levels of O − 2 and H 2 O 2 in the leaves of both the SY-MY13 and SY-XT1 inbred lines used in the current study (Figures 2C,D), which also demonstrated the histochemical staining of O − 2 and H 2 O 2 at the tissue level in the leaves of waxy corn (Figures 2A,B).…”
Section: Discussionmentioning
confidence: 99%
“…The crop stress index (CSI) and relative tolerance index (RTI) are used to determine if the treatments evaluated help to mitigate different stresses (abiotic and biotic) and have a positive effect on plant physiology (Castro-Duque et al, 2020;Chávez-Arias et al, 2020). CSI values can range between zero and one, representing the non-stressed and stressed conditions, respectively (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that waterlogging had a grave effect on stomach traits of plants which blocked the uptake of CO 2 , and here impeding the photosynthesis, and reducing the dry matter accumulation eventually. It has been demonstrated that H 2 O 2 priming was conducive to regulate stomatal characteristics, thus improving the gas exchange characteristics of leaves under waterlogging conditions (Castro-Duque et al, 2020). This study showed that the stomatal density of leaves reduced considerably and the stomatal size increased significantly in H 2 O 2 priming/waterlogging-stress plants.…”
Section: Correlation Analysismentioning
confidence: 62%
“…Studies have shown that exogenous H 2 O 2 could be used as a signal molecule to alleviate the effects of waterlogging on plants by regulating PSII efficiency and protecting chloroplasts (Castro-Duque et al, 2020;Hasanuzzaman et al, 2020). H 2 O 2 priming significantly increased the RC/CSm, indicating that H 2 O 2 priming protected the PSII reaction center.…”
Section: Discussionmentioning
confidence: 98%